A Meta-Analysis of the Correlates of Educational and Vocational Goals for Latina/o Students. (February 2019) - Risco, Cristina M.; O'Brien, Karen M.; Grivel, Margaux M.; Castro, Janice E.
Among Latina/o Americans, the fastest growing segment of the U.S. population, disparities exist in educational and career attainment. The emergence of research on Latina/o students has resulted in varied findings that make it difficult to draw conclusions as to which predictors are most closely associated with goal outcomes for this population. Using meta-analytic techniques, the current study examined the magnitude, direction, and heterogeneity of effect sizes across multiple educational and vocational goal outcomes for Latina/o students (i.e., educational/vocational aspirations, expectations, goals/plans, and persistence). Across 34 independent samples from 33 studies, career-related self-efficacy, peer support, adult support, barriers, and Anglo acculturation had moderate effects on at least one of the outcomes, with career-related self-efficacy and peer support being moderately related to two or more outcomes. If replicated, this research suggests that interventions focused on career-related self-efficacy and peer support could enhance the development of educational and career goals for Latina/o students.